PENGARUH FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN: Studi Kasus pada Salon Anne Beauty House Citraland, Kec. Benowo, Surabaya - Luluk Febianti Mulyasari; Hesti Pandu Widodo; Tjandra Wasesa (Jurnal Mahasiswa Manajemen dan Akuntansi, 2022)
This study aims to examine and analyze the effect of facility and service quality on customer satisfaction (study at salon Anne beauty house, Citraland, Benowo District, Surabaya). The type of research used in this study is to use descriptive research with a quantitative approach. The sampling technique that is accidental sampling amounted to 112 respondents. The datasets in this study were analyzed using the multiple linear regression test in SPSS version 26. It is well established through data analysis that both facility and service quality have a favorable and significant influence on customer satisfaction. Customer happiness is influenced positively and significantly by amenities and service quality. 44.8 percent of the independent factors in this study have an impact on customer satisfaction. The rest of the 55.2 percent is influenced by other factors that weren't in this study.